Words of Power: Ḥurūfī Teachings between Shi‘ism and Sufism in Medieval Islam - Sajjad Rizvi (International Institute of Islamic Thought, 2017)
The study of Islamic intellectual history, while existing in pockets of scholarship before, has increasingly become a dominant aspect of the study of Islam. We have moved from some piecemeal approaches to the classical period to a more carefully nuanced and thick understanding of the middle period, that critical time from the wane of the Abbasids to the rise of the Gunpowder Empires. In particular, the “Chicago school” has expended a great deal of effort in making sense of the critical messianic moment from around the time of Timur (1336-1405), the “lord of the junction,” to the “messianic sovereigns” of the Timurid and later Ottoman, Safavid, and Mughal empires. The book under review concerns one of the key intellectual developments of that period, namely, esoteric political theology and lettrism (‘ilm al-ḥurūf), which later informed similar developments in the sixteenth and seventeenth centuries. It gives us one, albeit marginal and rather antinomian, glimpse into the importance of the esoteric and occult learning that was a critical element of the scholarly underground even among elites throughout the middle and early modern periods in the world of Islam. Mir-Kasimov’s magisterial and highly textual study of Fazlallah Astarabadi (d. 1394) and his Hurufiyyah movement, neither mainstream Shi‘i nor Alid-loyalist Sufis nor even complete esotericists beyond the pale of Islam, contributes to the processes by which elite discourses on hermeneutics of reading the word and the world filtered into more subaltern and vernacular understandings of the cosmos and the human within and the divine both within and without ...